Economic Impact of the Emission-Reduction Policy: GTAP-E Model - Wuri, Josephine; Hardanti, Yuliana Rini; Rubiyatno, Rubiyatno; Ernawati, Maria Theresia; Kristianti, Ni Kadek Ayu (International Journal of Energy Economics and Policy, 2025)
Increasing greenhouse gas (GHG) emissions is a severe global health and well-being problem. Countries around the world are striving to overcome climate change-related problems. This study analyzes the economic impact of Indonesia’s emission-reduction policy of a carbon tax along with B40 renewable energy and trade regulation policies. This study uses a general equilibrium approach with several simulations of the Global Trade Analysis Project-Energy (GTAP-E) model. The GTAP-E approach analyzes the interaction between trade and energy policies. The GTAP-E model can simulate specific policies in government plans to assess their impact on macroeconomic conditions, bilateral trade, and the energy sector. The study results show that emission-reduction and trade regulation policies decrease inflation rates, economic growth, and welfare. According to bilateral trade research, Indonesia’s crude palm oil (CPO) exports to India and China have increased, producing a trade surplus. This result demonstrates an increase in trade competitiveness despite trade regulations. These findings reveal that, while emission-reduction policies can impact economic growth in the short term, they can also boost international trade positions, support the transition to a low-carbon energy system, and achieve sustainable economic development.